Sincronização temporal para dispositivos com conexão sem fio de baixo consumo de energia - Nascimento, Fernando Biazi (2014)
The present work consists of an implementation of time distribution protocol based on PTP disclosed in the IEC 61588:2009 / IEEE 1588-2008 standard to be used in low-power wireless devices. The distribution of time is important to determine the order of occurrence of events marked in distinct counts that can then be related. And the problems of lack of synchronicity are evident in circumstances ranging from the study of historical facts up to the investigation of intruders in modern equipments connected to the internet. The work included development of a completely new software for the microcontroller MSP430F2274TM using the CC2480TMnetwork controller. The implementation of the protocol considers one of the mechanisms described by the standard and remains very close to it, not fully conformant mainly because of lack of resources on the used device, but the expected behavior was kept. The devices synchronize the time between them and sintonize their time counting, in a way to reduce, as much as possible, the adjustments of further synchronizations.